Progress in Allogeneic Hematopoietic Cell Transplantation in Adult T-Cell Leukemia-Lymphoma - Utsunomiya, Atae (Frontiers in Microbiology, 2019)
The prognosis of aggressive adult T-cell leukemia-lymphoma (ATL) remains poor because of frequent infections and drug resistance. Dose-intensified chemotherapy followed by autologous stem cell transplantation failed to improve the prognosis of patients with ATL; however, we first revealed that allogeneic hematopoietic cell transplantation (allo-HCT) might improve their prognosis. We showed that reduced-intensity stem cell transplantation using peripheral blood was feasible for elderly patients. Further, the prognosis of patients in remission, who receive cord blood transplantation, has been recently improved and is equivalent to that of patients who receive transplants from other stem cell sources. As for the timing of HCT, the patients who underwent transplantation early showed better outcomes than those who underwent transplantation late. Based on the analysis of patients with aggressive ATL, including those who received transplants, we identified five prognostic factors for poor outcomes: acute-type ATL, poor performance status, high soluble interleukin-2 receptor levels, hypercalcemia, and high C-reactive protein level. Next, we developed a new prognostic index: the modified ATL-PI. The overall survival (OS) rates were significantly higher in patients who underwent allo-HCT than those who did not in the intermediate and high-risk groups stratified using the modified ATL-PI. Two new anti-cancer agents, mogamulizumab and lenalidomide, were recently approved for ATL patients in Japan. They are expected to induce longer survival in ATL patients when administered along with transplantation. However, a retrospective analysis that the risk of severe, acute, and corticosteroid-refractory graft-versus-host disease was higher in patients who received mogamulizumab before allo-HCT, and that mogamulizumab might increase the transplant-related mortality (TRM) rates and decrease the OS rates compared to those of patients who did not receive mogamulizumab. However, our recent study showed that administration of mogamulizumab before allo-HCT tended to improve the survival of patients with ATL. In conclusion, allo-HCT procedures for patients with aggressive ATL have considerably progressed and have helped improve the prognosis of these patients; however, many concerns still remain to be resolved. Further development of allo-HCT by using new molecular targeting agents is required for the improvement of cure rates in patients with ATL.